FRI0164 Predictors of loss of clinical remission with etanercept 50 mg, 25 mg or placebo combined with methotrexate in moderate rheumatoid arthritis patients: Results of the preserve trial. (23rd January 2014) - Smolen, J.S.; Szumski, A.; Koenig, A.S.; Jones, T.V.
Abstract : Background: Achievement of clinical remission is an essential target for treatment of rheumatoid arthritis (RA). 1 However, once remission is achieved, rheumatologists face the challenge of maintaining it while considering means to limit dosages and duration of treatments. Yet, little information is available about factors predictive of loss of remission when decreasing or stopping therapies. 2 Objectives: To assess demographic/disease characteristics that may predict loss of remission in pts with moderately active RA who continued etanercept (ETN) 50 mg QW+methotrexate (MTX; E50/M), reduced ETN from 50 mg to 25 mg QW+MTX (E25/M), or replaced ETN with placebo+MTX (P/M) over 52 wks after induction of initial response. Methods: Pts with moderately active RA (3.236 wks of open-label E50/M (Period 1 [P1]) were randomized to double-blind treatment with E50/M, E25/M, or P/M for 52 wks (Period 2 [P2]; N=604). In pts who achieved DAS28 remission (DAS28 <2.6) at wk 36, analyses of predictors for loss of remission included P1 baseline demographic/disease characteristics, P2 baseline disease characteristics, and P1 remission duration, adjusted for wk 36 DAS28. Cox proportional hazards modeling was conducted; given previously reported P2 finding of superior remission rates with E50/M or E25/M vs P/M, separate models were used for each treatment group. Results: Failing to achieve a sustained remission in P1 was the strongest predictor of loss of remission in P2 in each treatment group, with hazard ratios [95% CI] of: E50/M, 2.19 [1.37–3.51]; E25/M, 2.45 [1.41–4.25]; P/M, 1.67 [1.13–2.47]). Mean wk 36 DAS28 was also a predictor of loss of remission. Further analysis showed that in all treatment groups, pts who achieved DAS28 remission only at wks 28 and 36 or only at wk 36, vs at wks 12, 20, 28, and 36, were significantly more likely to lose DAS28 remission through wk 88 (table ). At wk 88, 29%, 34%, and 65% in the E50/M, E25/M, and P/M groups lost DAS28 remission (LOCF). Conclusions: Failure to achieve sustained remission over wks 12-36 of P1 was consistently associated with loss of remission through wk 88 with all treatment regimens. Loss of remission occurred at wk 88 in approximately one-third of patients in the full- and reduced-dose etanercept-MTX groups and two-thirds in the MTX-only group. Further analyses will explore relationships between changes in acute phase reactants/joint counts during P2 and loss of remission. References: Ann Rheum Dis. 2010; 69:631. Arthritis Res Ther. 2008;10:208. Disclosure of Interest: J. Smolen Grant/Research support from: Pfizer Inc, Consultant for: Pfizer Inc, A. Szumski Employee of: Pfizer Inc, A. Koenig Shareholder of: Pfizer Inc, Employee of: Pfizer Inc, T. Jones Shareholder of: Pfizer Inc, Employee of: Pfizer Inc